PENGARUH PEMASARAN DIGITAL DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MAKANAN BEKU DI KOTA BEKASI - Tatag Herbayu; Sekti Aryo Sumbodo (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2024)
The analyze the influence of digital marketing and product quality on Frozen Food purchasing decisions at Bekasi City. This research is included in the category of causal associative research using a quantitative approach. The population in this study were consumers who purchased Frozen Food in Bekasi City. The sampling technique used incidental sampling technique. The analytical method uses simultaneous and partially linear regression analysis. The results showed that in simultaneous or partially ways the digital marketing and product quality have a positive and significant on purchasing decisions at Bekasi City.